Computerized tomography based tumor-thickness measurement is useful to predict postoperative pathological tumor thickness in oral tongue squamous cell carcinoma. Issue 1 (December 2015) - Madana, J.; Laliberté, Frederick; Morand, Grégoire; Yolmo, Deeke; Black, Martin; Mlynarek, Alex; Hier, Michael
Abstract Background Tumor thickness has been shown in oral tongue squamous cell carcinoma (OTSCC) to be a predictor of cervical metastasis. The postoperative histological measurement is certainly the most accurate, but it would be of clinical interest to gain this information prior to treatment planning. This retrospective study aimed to compare the tumor thickness measurement between preoperative, CT scan, and surgical specimens . Methods We retrospectively included 116 OTSCC patients between 2001 and 2013. Thickness was measured on computer tomography imaging and again surgical specimens. Results The median age was 66 years. 62.8 % of patients were smokers with a mean of 31.4 pack-years. Positive nodal disease was reported in 41.2 %. Mean follow-up time was 33.1 months. The correlation between CT scan-based tumor thickness and surgical specimens based thickness was significant (Spearman rho = 0.755, P < 0.001). Conclusion Tumor thickness assessed by CT scan may provide an accurate estimation of true thickness and can be used in treatment planning.